Penerapan Manajemen Kinerja pada Usaha Mikro Amanah Yogurt Boyolali - Medya Wulandari; Rosita Rahmawati; Luthfi Naimah (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the implementation of performance management at the micro–enterprise AMANAH YOGURT, located in Candimulyo, Kiringan, Boyolali. The business employs 11 workers with specific task divisions: 7 in packaging, 1 in production, 2 in marketing responsible for promotion and advertising, and 1 supervisor who monitors the production process while also assisting in production ac,tivities. The daily production capacity reaches 500 packs during peak demand and 350 packs under normal conditions. This research applies a descriptive qualitative approach through observations and informal interviews with the owner and employees. The findings indicate that AMANAH YOGURT has implemented performance management through the application of production SOP, clear task distribution, informal evaluative communication between the owner and employees, as well as consistent adherence to hygiene standards and product quality. AMANAH YOGURT products have been distributed across Java Island, Bali, and even Mataram through bus logistics, travel services, and direct delivery for nearby areas. Halal certification and BPOM authorization further enhance consumer trust and strengthen the competitiveness of the business.